CHATGPT IN HIGHER EDUCATION: A REVOLUTION IN WRITING OR A RISK TO ORIGINALITY? - Sohibul Hairi; Arisandi Setiawan; Anandha Dewi P (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2025)
The integration of artificial intelligence (AI), particularly ChatGPT, into higher education has sparked critical discussions about its role in supporting students’ academic writing, especially in enhancing logical reasoning—a fundamental component of scholarly discourse. This study aims to investigate the effectiveness of ChatGPT in fostering students’ ability to construct coherent and well-reasoned arguments in academic contexts. Using a mixed-methods approach, the research involved 25 undergraduate students from an English Education Program with prior experience using AI writing tools. Data were collected through surveys, semi-structured interviews, and comparative analysis of student writing with and without ChatGPT assistance. Quantitative analysis revealed a high adoption rate of ChatGPT for tasks such as argument structuring, idea generation, and proofreading. Qualitative findings highlighted that student perceived significant improvements in clarity, coherence, and logical flow when using AI tools. Thematic analysis identified key benefits, including real-time feedback, diversified perspectives, and enhanced writing fluency. However, students also expressed concerns about over-reliance, superficial reasoning, and diminished originality. Comparative analysis showed that AI-assisted essays demonstrated greater structural coherence but required manual refinement for complex reasoning. While ChatGPT provided consistent and immediate feedback, human instructors were valued for their depth, contextual insight, and critical engagement. Limitations included the AI’s lack of deep comprehension, occasional inaccuracies, and generic responses, especially regarding nuanced topics. Students adopted strategies such as cross-checking AI outputs, integrating peer reviews, and limiting AI use to early writing stages to maintain academic integrity. In conclusion, while ChatGPT serves as a valuable supplementary tool for enhancing logical reasoning in academic writing, its effectiveness depends on critical engagement and balanced integration with traditional pedagogical approaches. The findings underscore the need for informed policies and ethical frameworks to guide responsible AI use in higher education.